Convolutionally coded frequency-hopping communications with nonideal interleaving - Laufer, S.; Reichman, A. (IEEE journal on selected areas in communications, 1990)
The interleaving span of coded frequency-hopped (FH) systems is often constrained to be smaller than the decoder memory length, i.e. nonideal interleaving is performed. An upper bound on the performance of a Viterbi decoder of a convolutional code with nonideal interleaving is presented. A soft decision diversity combining technique is introduced, and the performance of combined convolutional and diversity coding subject to worst-case partial band noise jamming is investigated. Optimization of the FH system performance subject to constraints of allowed delay and synthesizer settling time provides the best combination of interleaving span and hopping rate. The FH system considered employs M-ary frequency-shift key (MFSK) modulation and noncoherent demodulation with 2-b soft decision based on Viterbi's ratio-threshold technique.< >